2011
DOI: 10.1108/00251741111130887
|View full text |Cite
|
Sign up to set email alerts
|

Theory X/Y assumptions as predictors of managers' propensity for participative decision making

Abstract: Purpose -This study aims to explore whether McGregor's theory X/Y assumptions are determinants of managers' propensity for participative decision making (PDM). Design/methodology/approach -Surveys measuring theory X/Y assumptions and propensity for PDM were administered to 144 full-time managers from divergent industries across the USA. The hypotheses were tested using linear regressions. Findings -Results generally support McGregor's assertion that managers' theory X/Y assumptions are linked to PDM. Findings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 27 publications
0
30
0
Order By: Relevance
“…It eases supervisors to inspire them to continue to professionally grow further and adopt theory Y style of management. Russ (2011) argues that managers adopting theory X perceive participative decision making negatively and those adopting Theory Y perceive it positively. However, Supervisors in CTEVT despite being inclined to embracing the theory Y are unable to fully adopt principles of this theory.…”
Section: Discussionmentioning
confidence: 99%
“…It eases supervisors to inspire them to continue to professionally grow further and adopt theory Y style of management. Russ (2011) argues that managers adopting theory X perceive participative decision making negatively and those adopting Theory Y perceive it positively. However, Supervisors in CTEVT despite being inclined to embracing the theory Y are unable to fully adopt principles of this theory.…”
Section: Discussionmentioning
confidence: 99%
“…The general message in Theory X and Y is that some leaders (Type X) prefer to be directive, solve problems, and issue orders, with little or no involvement of their employees other than to follow those orders, while other leaders (Type Y) work better in a team setting, and share responsibilities and functions with followers (Russ, 2011).…”
Section: An Overview Of Leadership Qualitiesmentioning
confidence: 99%
“…More importantly, the Theory Y assumptions were negatively related to the anxious style and positively related to the supportive, impression leaving, and non-verbally expressive styles. In a recent study, Russ (2011) demonstrated the effect of managers' Theory X and Y assumptions on participative decision making.…”
Section: Mcgregor's Theory X and Ymentioning
confidence: 99%
“…More recent studies have indicated the importance of managers' Theory X and Y assumptions in a work setting (Larsson et al, 2007;Russ, 2011;Sager, 2008;S¸ahin, 2012). However, there is less research on the effect of managers' Theory X and Y assumptions on employees' attitudes and behaviors.…”
Section: Introductionmentioning
confidence: 99%